Impact of Contextual Teaching Learning Model to Science Process Skills and Scientific Attitudes of Students - Kadmayana Kadmayana; A Halim; Mustafa Mustafa; Suhrawardi Ilyas (Jurnal Penelitian Pendidikan IPA, 2021)
Science process skills are skills that need to be developed in students in learning science such as science. The low level of KPS on the science concept is influenced by the learning model which emphasizes the aspects of receiving full information from the teacher. Student KPS is also dominated by an increase in scientific attitudes that require students to show their sensitivity to the surrounding environment. This study aims to determine science process skills and increase students' scientific attitudes through the implementation of the contextual teaching and learning model at MTsS Muta'allimin Aceh Besar. The method used in this study was an experiment with a one-group pretest-posttest design. The instruments used were observation sheets and questionnaires. The results showed that the implementation of the CTL learning model could improve students' KPS in both categories with an average score of 71-85 and very good categories with an average score of 86. In addition to improving the KPS learning model implementation, CTL can also improve students' scientific attitudes with a value N-gain average of 0.63 including the moderate category. The results of the improvement obtained by the average student are in good categories with an average score of 71-85 then the category is very good with an average score.  86-100. The conclusion in this study proves that the CTL model can improve student learning skills and scientific attitudes, especially the material of vibration, waves, and sound